Localized propranolol delivery from a copper-loaded hydrogel for enhancing infected burn wound healing via adrenergic β-receptor blockade - Wenzhe Sun; Hongwei Lu; Pengqin Zhang; Lian Zeng; Bing Ye; Yi Xu; Jianan Chen; Peiran Xue; Jialin Yu; Kaifang Chen; Bin Wu; Xiao Lv; et al. (Materials Today Bio)
Severe burn injuries immediately trigger a sustained systemic and local stress response. During this process, the sympathetic nervous system releases large amounts of catecholamines, which bind to β-adrenergic receptors (β-AR) on cell membranes, negatively affecting skin regeneration. Additionally, recurrent bacterial infections make burn wounds difficult to treat, posing significant and ongoing challenges to burn care. To address these challenges, we pioneered the study of locally delivered propranolol for burn wound treatment, revealing its ability to antagonize norepinephrine (NE) and regulate the sympathetic nervous system. In this study, a Cu2⁺-loaded anti-sympathetic hydrogel (copper ion cross-linked propranolol@gelatin/alginate, PNL@GA-Cu) was developed to remodel the challenging neuromodulatory microenvironment and accelerate the repair of the infected burn wound. The hydrogel system releases Cu2⁺ and propranolol simultaneously during degradation, synergistically acting on local wound tissue. Cu2⁺ exhibits dual effects of antibacterial activity and promoting angiogenesis, effectively killing Staphylococcus aureus and Escherichia coli while enhancing the expression of angiogenesis-related genes (CD31, VEGF). Meanwhile, propranolol can counteract the inhibitory effects of NE simulated chronic stress microenvironment on angiogenesis and mitigate sympathetic nerve innervation during the early stages of wound healing. Finally, the PNL@GA-Cu hydrogel significantly promoted the repair of third-degree full-thickness burns in SD rats. Approaches targeting the neural microenvironment for burn wound treatment has not been previously addressed in the literature. The anti-sympathetic PNL@GA-Cu hydrogel offers a promising strategy for treating infected burn wounds. Remodeling the neuromodulatory microenvironment could be an emerging strategy in tissue engineering.